Development of Genially-based interactive multimedia for junior high school English learning - Dewi Bernike Tampubolon; Sahat Siagian; Abdul Hasan Saragih (Universitas Pendidikan Indonesia, 2025)
The integration of technology into education is crucial for enhancing learning quality and student engagement. Many junior high school students face difficulties in learning English, particularly in writing descriptive texts, due to the lack of interactive and engaging media. This study aims to develop interactive learning multimedia using the Genially platform to support English learning at SMP N 2 STM Hulu. The research employed the ADDIE instructional design model, while the product development process followed the Multimedia Development Life Cycle (MDLC) model. The media features descriptive text materials enhanced with animations, games, quizzes, and videos to support student comprehension and motivation. Validation by subject matter experts indicates high feasibility. Field trials showed practicality, and results from the independent t-test indicated a significant difference in learning outcomes between the experimental and control classes. These findings suggest that Genially-based multimedia developed through MDLC within the ADDIE framework is a highly feasible, practical, and effective tool to enhance the quality of English language learning in junior high schools. Abstrak Integrasi teknologi dalam pendidikan menjadi kebutuhan penting untuk meningkatkan kualitas pembelajaran dan keterlibatan peserta didik. Banyak peserta didik SMP mengalami kesulitan dalam pembelajaran Bahasa Inggris, khususnya dalam menulis teks deskriptif, karena kurangnya media yang interaktif dan menarik. Penelitian ini bertujuan untuk mengembangkan multimedia pembelajaran interaktif menggunakan platform Genially untuk mendukung pembelajaran Bahasa Inggris di SMP N 2 STM Hulu. Penelitian ini menggunakan model desain pembelajaran ADDIE, sementara proses pengembangan produk multimedia mengikuti model Multimedia Development Life Cycle (MDLC). Media yang dikembangkan memuat materi teks deskriptif dengan animasi, permainan, kuis, dan video untuk meningkatkan pemahaman dan motivasi peserta didik. Hasil validasi ahli materi, ahli media, dan ahli desain pembelajaran menunjukkan kelayakan tinggi. Uji coba lapangan menunjukkan kepraktisan dan memperlihatkan hasil uji t independen menunjukkan perbedaan signifikan antara hasil belajar kelas eksperimen dan kelas kontrol. Temuan ini menyimpulkan bahwa multimedia berbasis Genially yang dikembangkan melalui model MDLC dalam kerangka ADDIE sangat layak, praktis, dan efektif untuk meningkatkan kualitas pembelajaran Bahasa Inggris di tingkat SMP. Kata Kunci: Genially; MDLC; multimedia interaktif; pembelajaran bahasa Inggris